"No signs of rape": corroboration, resistance and the science of disbelief in the medico-legal jurisprudence of Bangladesh. Issue 2 (1st January 2022) - Huda, Taqbir
Abstract: A major impediment to justice for rape in Bangladesh is the colonial rule of corroboration, which requires judges to verify the truthfulness of a rape complainant's testimony with other evidence. Medical evidence is the most commonly sought mode of corroboration and can be used to contradict the complainant's own testimony. The corresponding rule of resistance in turn guides how the rule of corroboration takes on a scientific character, whereby injuries in specific parts of the complainant's body are sought by doctors and judges as corroborative "signs of rape". If no "signs of rape" are found, this observation is then noted in the medical report and used to discredit the testimony of a rape complainant, by indicating that either the sexual intercourse was consensual or the rape accusation is false. This paper shows how the unfettered operation of these two rules gives birth to the "science of disbelief" in rape cases, whereby the institutional disbelief in a rape complainant's testimony is justified on ostensibly scientific grounds and largely restricts their right to seek justice. It illustrates how the science of disbelief was created and preserved through successive legal and institutional reforms in Bangladesh. This paper challenges the long-held yet seemingly unquestioned notion in Bangladesh that medical evidence should be the primary basis through which rape can be proved in court by analysing the pernicious jurisprudence and legal standards this assumption has created.